Powieść „Inny” Jurija Mamlejewa wobec artystycznego poznania Fiodora Dostojewskiego - Przybysz, Anna Katarzyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The aim of this article is to show the undeniable influence of Fyodor Dostoyevsky’s artistic method on Yuri Mamlejev’s literary works in particular in relation to his novel The Other. Relying on these determinants of fantastic realism, which for many researchers are referred to as the most significant elements of Dostoyevsky’s artistic method, we make an attempt to show that the carnival which combines the two orders in the works of the 19th century writer: the real (scientific) and the surreal (magic), makes the fantasy become an integral part of the surrounding space. Simultaneously the concept of fiction should be understood through such categories as: paradoxicality, iconicity, a word as a vessel, sleep, hallucinations, picture in picture, doppelgänger that foster deep psychological self-understanding of the entity. In the article we aim to expose some of the abovementioned categories of constructing the world of Dostoyevsky’s works and making up, as defined by the author himself “the realism of higher sense” which, in a slightly modified form, although still clearly visible, is also reflected in Mamleev’s artistic method – metaphysical realism. The main emphasis is put on the categories of sleep and doppelgänger which are the clearest examples of Yuri Vitalevich’s inspiration.